Evaluation of Combined Effect of Mercerized and Dyed Yarns on Physical Properties of Plain Single Jersey Knitted Fabrics. (13th December 2015) - Elrys, S. M.; El-Hossini, A.; EL-Hadidy, A. M.
Abstract : A combined effect of mercerized and dyed yarns on physical properties of plain single jersey knitted fabrics has been studied. Plied cotton yarn was produced and mercerized at different NaOH concentrations and temperatures. Then, this yarn was bleached and dyed with two types of dyes, vat dyeing and reactive dyeing. Each of mechanical and color properties were measured to these treated yarns. Plain single jersey knitted fabrics were produced from these treated yarns. The total evaluation of the properties for plain single jersey fabrics was measured by using radar chart method. It was found that the highest area of radar chart, which represents the total physical properties, is achieved at 32°Be′, in case of vat dyeing. Besides, analysis of variance (AVOVA) and MANOVA were applied to illustrate which of the properties would be affected by NaOH con. and types of dyeing for yarns and fabrics.